THE EFFECTS OF NI NANOPARTICLE ADDITIVES ON THERMODYNAMIC EVENTS IN COMMERCIAL NI BASED BRAZE ALLOY - (:unkn) unknown (My University, 2024)
The use of nanomaterials in brazing applications has become more prevalent with the increasing understanding of the underlying thermodynamic events during the brazing process. Their influence on an already modified system, via melting point depressants, is not well understood. In this investigation, the influence of both nanoparticle size and weight percent of nanoparticle additive are studied to determine the relationship on thermodynamic events. Differential scanning calorimetry was used to measure the energy flow throughout the system during the brazing events. Scanning electron microscopy was used qualitatively to view the resulting brazed region. The results indicate a direct relationship between nanoparticle additive size and weight percent and the resulting melting and solidification temperatures. The resulting enthalpy of the braze event also decreased in magnitude with the increase in weight percent of nanoparticle additive. Understanding the thermodynamic effects of nanoparticle additives on commercial alloys containing melting point depressants can lead to a “best of both worlds” scenario.
Keywords: braze; commercial; DSC; nanoparticle; nickel